PENGARUH MOTIVASI TERHADAP KINERJA PEGAWAI DI INSPEKTORAT DAERAH PROVINSI SULAWESI TENGAH - Wahyulianti, Dwi (Katalogis, 2015)
This study aims to assess and analyze the effect of motivation on employee performance Regional Inspectorate of Central Sulawesi Province. This type of research using this type of survey quantitative approach, measure theory of motivation by Maslow in Mangkunagara (2005: 63), comprising: physiological needs, safety, social, respect and self-actualization. Medium theory of performance based on the opinions Bernardin and Russel in Sulistiyani (2004: 83) consisting of: quality, quantity, timeliness, effectiveness and independence of work commitment. Based on the results of a simple regression analysis, it was concluded that, on the calculation on the independent variable motivation with the dependent variable employee's performance Regional Inspectorate of Central Sulawesi Province, obtained Fhitung = 58 547 on a real level Ã¡ = 0.05 or 0.05 Ë‚ F Siq. The table also shows that the value of the significance F = 0.000. It can be stated that the independent variables (motivation) has influence on variable dependent significant (performance). Thus, the second hypothesis which states that, motivation and positive effect on employee performance significant Regional Inspectorate of Central Sulawesi province, based on the F-test resultsÂ proved.